The most influential 4PS towards student enrolment : the case of Cosmopoint International College of Technology / Haafiza Nadia Asan - Asan, Haafiza Nadia (2014)
The purpose of this project paper is to stude the most influential 4Ps which leads to students' enrolment in Cosmopoint International College of Technology Kota Kinabalu (CICT KK) . The researcher is focusing on the The Traditional Marketing Mix which is the product, place, price and promotion. Quantitative data collection method and the simple random sampling is used to aid the research. The target population for the research is the active students of CICT KK. 90 questionnaires will be distributed to the respondents and will be analysed by using the SPSS software.